Motivational orientations of learning Japanese as a foreign language among undergraduates in a public university in Malaysia / Kuldip Kaur Maktiar Singh … [et al.] - Maktiar Singh, Kuldip Kaur; Loh, David Er Fu; Leong, Irene Yoke Chu; Phang, Yook Ngor; Chan, Yann Seng; Abd Hamid, Nurul Atiqah (Akademi Pengajian Bahasa, 2021)
Motivation is a key factor in learning a foreign language (FL). This study investigated the instrumental, integrative and attitudinal motivation level of students learning Japanese as a FL in a public university in Malaysia. A survey questionnaire based on Gardner’s (1985) AMTB (Attitude/Motivation Test Battery) and Dornyei’s (1994) Attitudinal Motivation was given to 171 undergraduates. Descriptive and Inferential statistics were used to analyse the data. The results of the study indicated that the FL learners were generally highly motivated to learn Japanese as a foreign language. Moreover, their integrative and attitudinal motivational levels were similarly high and slightly higher than their instrumental motivation. There were also statistically significant differences among the three subscales of attitudinal motivation viz. teacher-specific, course-specific and group specific. They were more oriented towards teacher-specific and course-specific attitudinal motivation than group-specific attitudinal motivation. The implications for EFL teachers and curriculum developers are that it would improve foreign language learning courses in future by designing suitable lessons and preparing appropriate materials and activities.